The link between tectonics and sedimentation in asymmetric extensional basins: Inferences from the study of the Sarajevo-Zenica Basin. (May 2017) - Andrić, N.; Sant, K.; Matenco, L.; Mandic, O.; Tomljenović, B.; Pavelić, D.; Hrvatović, H.; Demir, V.; Ooms, J.
Abstract: The coupled tectonic and depositional history of extensional basins is usually described in terms of stratigraphic sequences linked with the activity of normal faults. This depositional-kinematic interplay is less understood in basins bounded by major extensional detachments or normal fault systems associated with significant exhumation of footwalls. Of particular interest is the link between tectonics and sedimentation during the migration of normal faulting in time and space across the basin. One area where such coupled depositional-kinematic history can be optimally studied is the Late Oligocene - Miocene Sarajevo-Zenica Basin, located in the Dinarides Mountains of Bosnia and Herzegovina. This intra-montane basin recorded Oligocene – Pliocene sedimentation in an endemic and isolated lake environment. We use field kinematic and sedimentological mapping in outcrops correlated with existing local and regional studies to derive a high-resolution evolutionary model of the basin. The novel results demonstrate a close correlation between moments of normal faulting and high-order sedimentological cycles, while the overall extensional basin was filled by a largely uni-directional sediment supply from the neighbouring mountain chain. The migration in time and space of listric NE-dipping normal faults was associated with a gradual shift of the sedimentological environment. Transgressive-regressive cycles reflect sequential displacements on normal faults and their footwall exhumation, defining a new sedimentological model for such basins. This Early - Middle Miocene extension affected the central part of the Dinarides and was associated with the larger opening of the neighbouring Pannonian Basin. The extension was preceded and followed by two phases of contraction. The Oligocene - Early Miocene thrusting took place during the final stages of the Dinarides collision, while the post-Middle Miocene contraction is correlated with the regional indentation of the Adriatic continental unit. This latter phase inverted the extensional basin by reactivating the inherited basal listric detachment. Highlights: Coupled tectonic and depositional model of asymmetric extensional basins. Distribution of transgressive-regressive cycles reflects migration of deformation across the basin. The final stages of Dinarides orogenic evolution are recorded in the basin.